Preconception Counseling in Patients with Hypothyroidism and/or Thyroid Autoimmunity - Mihaela Țarnă; Luminița Nicoleta Cima; Anca Maria Panaitescu; Carmen Sorina Martin; Anca Elena Sîrbu; Carmen Gabriela Barbu; Bogdan Pavel; Andreea Nicoleta Șerbănică; Simona Fica (Medicina, 2022)
Preconception counseling is an essential tool for preventing adverse pregnancy outcomes associated with thyroid dysfunction. The high prevalence of thyroid disease among women of reproductive age, and the increased risk of adverse pregnancy outcomes associated with thyroid dysfunction, emphasize the necessity for well-established screening and treatment criteria in the preconception period. We therefore conducted a literature review for relevant information on the screening, diagnosis and treatment of subclinical and overt hypothyroidism in women seeking pregnancy. While screening for thyroid disease is recommended only in the presence of risk factors, iodine supplementation should be recommended in most regions, with higher doses in areas with severe deficiency. Known hypothyroid women should be counseled about increasing their levothyroxine dose by 20–30% in the case of suspected or confirmed pregnancy (missed menstrual cycle or positive pregnancy test). Treating subclinical hypothyroidism appears to be beneficial, especially in the presence of autoimmunity or in patients undergoing artificial reproductive techniques. Regarding the management of TPOAb negative SCH women or euthyroid women with positive TPOAb, further research is necessary in order to make evidence-based recommendations.